A time-saving and cost-effective method to process alloys by Laser Powder Bed Fusion. (5th November 2019) - Bosio, Federico; Aversa, Alberta; Lorusso, Massimo; Marola, Silvia; Gianoglio, Dario; Battezzati, Livio; Fino, Paolo; Manfredi, Diego; Lombardi, Mariangela
Abstract: Definition of the main process parameters, laser power ( P ), scanning speed ( v ), hatching distance ( h d ) and scanning strategy useful for producing dense samples, is fundamental to develop novel alloy compositions for Laser Powder Bed Fusion (LPBF). The present work has two aims: on one side, to verify the processability of a new AlSi10Mg + 4Cu alloy of mixed powders by LBPF; on the other side, on the basis of the experimental analysis, to define a method for processing new alloys. Producing Single Scan Tracks (SSTs), samples with unidirectional scanning strategy and samples with 67° rotated scanning strategy, the proper P - v-h d combinations were identified reaching a final porosity lower than 1.5%. A scenario of hardness and build-up rate vs. energy density is given, to adopt the main process parameters suitable to maximize mechanical properties or productivity. According to the novel method, P - v-h d combinations can be defined through the production and characterization of SSTs and samples with 67° rotated scanning strategy. Through two production steps dense samples can be then obtained, allowing the development of new compositions saving time and reducing costs related to the powder usage. Graphical abstract: Unlabelled Image Highlights: A time- and cost-effective method to manufacture new alloys by Laser Powder Bed Fusion (LPBF) is proposed. Definition of main process parameters for processing new alloys for LPBF is achieved by means of Single Scan Tracks (SSTs). A proper overlap between nearby SSTs is the key for defining the proper hatching distance for high density massive samples. A scenario of hardness and productivity vs. energy density is given for a new Al alloy: AlSi10Mg + 4 wt% Cu mixed alloy.